Integrated linkage-driven dexterous anthropomorphic robotic hand - Kim, Uikyum; Jung, Dawoon; Jeong, Heeyoen; Park, Jongwoo; Jung, Hyun Mok; Cheong, Joono; Choi, Hyouk Ryeol; Do, Hyunmin; Park, Chanhun (Nature Communications, 2021)
Robotic hands perform several amazing functions similar to the human hands, thereby offering high flexibility in terms of the tasks performed. However, developing integrated hands without additional actuation parts while maintaining important functions such as human-level dexterity and grasping force is challenging. The actuation parts make it difficult to integrate these hands into existing robotic arms, thus limiting their applicability. Based on a linkage-driven mechanism, an integrated linkage-driven dexterous anthropomorphic robotic hand called ILDA hand, which integrates all the components required for actuation and sensing and possesses high dexterity, is developed. It has the following features: 15-degree-of-freedom (20 joints), a fingertip force of 34N, compact size (maximum length: 218 mm) without additional parts, low weight of 1.1 kg, and tactile sensing capabilities. Actual manipulation tasks involving tools used in everyday life are performed with the hand mounted on a commercial robot arm.
Keywords: Anthropometry; Biomechanical Phenomena; Equipment Design; Fingers; Hand; Hand Joints; Hand Strength; Humans; Range of Motion, Articular; Robotics; Touch